Novel Klebsiella pneumoniae K23-Specific Bacteriophages From Different Families: Similarity of Depolymerases and Their Therapeutic Potential - Gorodnichev, Roman B.; Volozhantsev, Nikolay V.; Krasilnikova, Valentina M.; Bodoev, Ivan N.; Kornienko, Maria A.; Kuptsov, Nikita S.; Popova, Anastasia V.; Makarenko, Galina I.; Manolov, Alexander I.; Slukin, Pavel V.; Bespiatykh, Dmitry A.; Verevkin, Vladimir V.; et al. (Frontiers in Microbiology, 2021)
Antibiotic resistance is a major public health concern in many countries worldwide. The rapid spread of multidrug-resistant bacteria is the main driving force for the development of novel non-antibiotic antimicrobials as a therapeutic alternative. Here, we isolated and characterized three virulent bacteriophages that specifically infect and lyse multidrug-resistant Klebsiella pneumoniae with K23 capsule type. The phages belonged to the Autographiviridae (vB_KpnP_Dlv622) and Myoviridae (vB_KpnM_Seu621, KpS8) families and contained highly similar receptor-binding proteins with polysaccharide depolymerase enzymatic activity. Based on phylogenetic analysis, a similar pattern was also noted for five other groups of depolymerases, specific against capsule types K1, K30/K69, K57, K63, and KN2. The resulting recombinant depolymerases Dep622 (phage vB_KpnP_Dlv622) and DepS8 (phage KpS8) demonstrated narrow specificity against K. pneumoniae with capsule type K23 and were able to protect Galleria mellonella larvae in a model infection with a K. pneumoniae multidrug-resistant strain. These findings expand our knowledge of the diversity of phage depolymerases and provide further evidence that bacteriophages and phage polysaccharide depolymerases represent a promising tool for antimicrobial therapy.